Reassessing “infrastructuring digital sovereignty”: digital self-determination as a set of infrastructure-embedded practices - Musiani, Francesca (Frontiers in Communication, 2025)
This perspective contribution takes stock of recent research conducted through the theoretical lens, grounded in science and technology studies (STS) and more specifically infrastructure studies, which I have previously defined as “infrastructuring digital sovereignty” (Musiani, 2022). With this concept, I address “digital sovereignty” beyond its strictly legal interpretations and its rhetorical uses in political discourses by understanding it “from within” as an ongoing series of negotiations, practices, struggles, and controversies embedded in infrastructures, their creation, their development, and their maintenance. The contribution will discuss how, via two recently started projects, French and global interdisciplinary teams seek to provide an empirical and theoretical understanding, informed by the social sciences, of digital sovereignty as a set of processes and co-constructed techniques, practices, and norms “in the making.”